Determinants of banking sector development in emerging economies: panel estimation - Donia, Lamia (AUC Knowledge Fountain, 2012)
The study provides new evidence on the determinants of banking sector development, using data from 18 emerging economies during 2000-2009. The study employs panel data analysis, namely Random Effect, Feasible Generalized Least Squares and Dynamic Generalized Method of Moments estimations. The empirical results demonstrate that rule of law; economic growth and workersâ remittances promote banking sector development. However, financial liberalization and liberal trade policies have an insignificant influence on banking sector development. Therefore, the study suggests that emerging countries, aiming at enhancing banking sector development, should establish strong institutional infrastructure; whereas financial liberalization and trade openness should come at a later stage. Finally, the study provides evidence on a complementary relationship between banking sectors and capital markets in emerging countries.